A pilot randomised controlled trial evaluating mini and conventional implant retained dentures on the function and quality of life of patients with an edentulous mandible. Issue 1 (December 2017) - Jawad, Sarra; Barclay, Craig; Whittaker, William; Tickle, Martin; Walsh, Tanya
Abstract Background Total tooth loss (edentulism) can be a debilitating condition, impacting on ability to chew, speak and interact with others. The most common treatment is with complete removable dentures, which may be successful, but in the lower jaw, bone resorption that worsens over time makes denture-wearing difficult. Two dental implants in the mandible to retain the lower denture has been advocated as the gold standard of treatment, but has not been universally provided due largely to financial constraints and also patient fear. Mini implants (MI) are cheaper and less invasive than conventional implants (CI), but may not have equivalent longevity. Therefore, it is unknown whether they represent a cost-effective treatment modality over time. The aim of this pilot randomised controlled trial was to assess the feasibility of carrying out a trial on this cohort of patients, and to inform the study design of a large multicentre trial. Methods Forty-six patients were randomly allocated to receive either two mini implants or two conventional implants in the mandible to retain their lower dentures. Quality of life (QoL) questionnaires, pain and anxiety scores, and an objective "gummy jelly" chewing test were carried out at multiple timepoints, along with detailed health economics information. Implants were placed one-stage, and an early loading protocol was utilised. Patients were reviewed 8 weeks post-placement, and finally at 6 months. Implant failure, recruitment and retention rates were recorded and analysed. Results The pilot study demonstrated that it is possible to recruit, randomise and retain edentulous (mainly elderly) patients for an implant trial. We recruited to target and retention rates were acceptable. The large number of questionnaires was onerous for participants to complete, but the distribution of scores and feedback from participants helped inform the choice of primary and secondary outcomes in a full trial. The chewing test was time-consuming and inconsistent. Implant failure rate was low (1/46). The data on indirect costs gathered at every visit was viewed as repetitive and unnecessary, as there was little or no change between visits. Conclusions The pilot study has shown that acceptable recruitment and retention rates are achievable in this population of patients for this intervention. The results provide valuable information for selection of outcome variables and sample size calculations for future trials. Trial registration (ISRCTN):87342238 Trial registration date: 05/07/2013.